Formulation of Alternative Islamic Education Through the Multiple Intelligences Approach at Boarding School - Ali Makki; Muhammad Fahmi Hidayatullah; Baharuddin Baharuddin; Basri Basri (STAI Hubbulwathan Duri, 2023)
Pesantren, as future Islamic education institutions, is based on community needs based on the dynamics of the morality of the developing generation. This study aims to reveal alternative Islamic education's hierarchy, formulas, and formulations in pesantren with a multiple intelligences approach. This research was conducted at Pondok Pesantren Puncak Darussalam Potoan Dajah Palengaan Pamekasan, which is capable of producing graduates with national and international contributions and achievements. The characteristics of this pesantren are able to accommodate the potential of santri through the multiple intelligences approach with varied activities representing the multiple intelligences of the santri. The chosen research technique employs a descriptive qualitative approach, specifically utilising a case study design. The data collection process encompasses various methods, including observation, interviews, and documentation. The study yielded findings about the hierarchical structure of alternative Islamic education, which was analysed through multiple intelligences theory, incorporating integrative, creative, and adaptive principles. The formula is organised in a systematic manner, incorporating many supporting materials that encompass the stages of input, process, output, and outcome. The formulation is evident in the design of learning activities that serve to strengthen and enhance the nine different types of intelligence.